INCREASING QUALITY OF THE PROCUREMENT PROCESS IN RUSSIA BY INTRODUCING THE SELECTION OF ELECTRONIC TRADING PLATFORMS FOR STATE AND MUNICIPAL PROCUREMENT - T. Lysenko (Вестник университета, 2018)
The paper is dealing with the history of establishment and development of the modern tendencies of the contract system in procurement for state and municipal needs through electronic trading platforms. The reasons for the selection of sites were specified, its main disadvantages were noted: lack of transparency and insufficient regulation. The importance of an independent technical audit of the ETP with publication of detailed report in the Internet was proven. The necessity of carrying out an open discussion of the proposed mechanisms for introducing an electronic trading platform selection system with the aim to increase the efficiency of the procurement process in Russia is justified.